Surgical management and outcome of grade-C pancreatic fistulas after pancreaticoduodenectomy: A retrospective multicenter cohort study. (August 2019) - Ma, Tao; Bai, Xueli; Chen, Wen; Lao, Mengyi; Jin, Gang; Zheng, Kailian; Fu, Deliang; Yang, Feng; Qin, Renyi; Li, Xu; Lou, Wenhui; Zhang, Lei; et al.
Abstract: Background: Management strategies for grade-C postoperative pancreatic fistula (POPF) following pancreaticoduodenectomy (PD) vary. The aim of this study was to evaluate surgical indications, approaches, and outcomes of grade-C POPF following PD. Materials and methods: The clinical data of grade-C POPF patients from 9 high-volume institutions between January 1, 2012 and December 31, 2016 were retrospectively reviewed. The indications and outcomes of different surgical strategies were analyzed. Risk factors for unfavorable outcomes were evaluated by multivariate regression analysis. Results: Out of 5115 patients that underwent PD, 68 were diagnosed as grade-C POPF, and 53 underwent re-laparotomy. Pancreas-preserving surgical strategies were mostly used in this cohort (96.2%). Postoperative hospital stay in the external wirsungostomy group tended to be shorter than the other two major surgical approaches (20 days vs. 38 days and 34.5 days). Mortality and morbidity were comparable among different surgical strategies. Prolonged high drain amylase level prior to the development of grade-C POPF was negatively associated with unfavorable outcomes after re-laparotomy (OR: 0.20, 95% CI: 0.05–0.82). Conclusion: Pancreas-preserving approaches were preferred for grade-C POPF in this multicenter database, although the choice of definite procedure differed according to different clinical scenarios. Longstanding high amylase drainage may predict better outcomes after re-laparotomy. Highlights: Pancreas-preserving approaches were preferred for grade-C postoperative pancreatic fistula (POPF). External wirsungostomy is a feasible and effective way to preserve the pancreatic remnant and to achieve damage control. Longstanding high amylase drainage may predict better outcomes after re-laparotomy for grade-C POPF.